The factor of delay in a system of coupled oscillators FitzHugh - Nagumo - S. D. Glyzin; E. A. Soldatova (Моделирование и анализ информационных систем, 2010)
The dynamics of two weakly coupled close oscillators FitzHugh - Nagumo occuring in the simulation of the electric impulse exchange between nerve cells is considered. The delay in a connecting element between two oscillators is taken into account. Despite of the weakness of interaction, it is shown by local asymptotic methods that the introduction of a delay leads to significant changes in the script of phase reconstructions. The corresponding numerical analysis allows us to demonstrate that the introduction of the appropriate delay let us avoid the situation of the coexistence of a stable synchronous cycle and nonsynchronous oscillations.